Krmarjenje v srednjem veku informacijske dobe - Kavčič-Čolić, Alenka (Knjižnica, 2007)
The article deals with the problem of long-term preservation of electronic resources. A brief overview of the practice in this field worldwide as well asin the National and University Library of Slovenia is given. Some of the foundations that were the starting point for legislative changes in the field of long-term preservation of electronic resources in Slovenia are presented as well as the new challenges that the National and University Library is facing in this regards.
Keywords: informacijska tehnologija; information technology; elektronski viri; digitalni arhivi; arhiviranje; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana